New Student Admission Using SAW Method at Darut Ta'lim Islamic Boarding School - Perkasa, Eza Budi; Irawadi, Syafrul; Yanuarti, Elly; Anisah, A; Romadiana, Parlia (IJISTECH (International Journal of Information System and Technology), 2023)
With current technological advances, it is certainly very easy for human work, an example of current technological advances is smartphones. This can be a development of a smartphone technology, namely the Android-Based New Student Admission Application with the Simple Additive Weighting (SAW) Method at Darut Ta'lim Islamic Boarding School in Kundi Village. This application is an application that aims to make it easier for prospective new students to be able to register online and be able to optimize the data collection process for prospective new students at Darut Ta'lim Islamic Boarding School in Kundi Village. The method used in this research is the Prototype Method which has four stages, namely the data collection stage, the rapid planning stage, the Prototype Design Stage and the Prototype Testing Stage. The quick planning stage uses UML (Unified Modelling Language) diagrams such as use case diagram, activity diagram, class diagram and sequence diagrams. The results obtained from this research is an application design that can be developed into an application made using Android Studio with Kotlin programming language and using PHP with MySQL database.